Analisis Pengaruh Tekanan Kerja Anoda Terhadap Performa Proton Exchange Membrane Fuel Cell (PEMFC) - Sibarani, Leo Obed Dwikyra; Sucipta, Made; Suryawan, I Gede Putu Agus (Teknik Desain Mekanika, 2024)
Abstract PEMFC is a device for converting energy from hydrogen energy into electrical energy through an electrochemical process. PEMFC is one of the technologies developed in overcoming environmental problems in the transportation sector that can be used as a driver of FCEV (Fuel Cell Electric Vehicle). The properties of the constituent components of PEMFC and reactant fluids are factors that affect the work of PEMFC, one of which is working pressure. This study was conducted to conduct research on the performance and flow phenomenon in PEMFC at various anode working pressures with the same load value of 1 A. The results of this study showed better performance in PEMFC with greater anode working pressure. In addition, at higher working pressures there is an increase in the distribution of reactants in MEA and an increase in reactions that occur at the cathode as indicated by the increasing production of water on the cathode side. Keywords: PEMFC, pressure